Library iris.bi.big_op

From stdpp Require Import countable fin_sets functions.
From iris.algebra Require Export big_op.
From iris.algebra Require Import list gmap.
From iris.bi Require Import derived_laws_later.
From iris.prelude Require Import options.
Import interface.bi derived_laws.bi derived_laws_later.bi.

Notations for unary variants
Notation "'[∗' 'list]' k ↦ x ∈ l , P" :=
  (big_opL bi_sep (λ k x, P%I) l) : bi_scope.
Notation "'[∗' 'list]' x ∈ l , P" :=
  (big_opL bi_sep (λ _ x, P%I) l) : bi_scope.
Notation "'[∗]' Ps" := (big_opL bi_sep (λ _ x, x) Ps%I) : bi_scope.

Notation "'[∧' 'list]' k ↦ x ∈ l , P" :=
  (big_opL bi_and (λ k x, P%I) l) : bi_scope.
Notation "'[∧' 'list]' x ∈ l , P" :=
  (big_opL bi_and (λ _ x, P%I) l) : bi_scope.
Notation "'[∧]' Ps" := (big_opL bi_and (λ _ x, x) Ps%I) : bi_scope.

Notation "'[∨' 'list]' k ↦ x ∈ l , P" :=
  (big_opL bi_or (λ k x, P%I) l) : bi_scope.
Notation "'[∨' 'list]' x ∈ l , P" :=
  (big_opL bi_or (λ _ x, P%I) l) : bi_scope.
Notation "'[∨]' Ps" := (big_opL bi_or (λ _ x, x) Ps%I) : bi_scope.

Notation "'[∗' 'map]' k ↦ x ∈ m , P" := (big_opM bi_sep (λ k x, P%I) m) : bi_scope.
Notation "'[∗' 'map]' x ∈ m , P" := (big_opM bi_sep (λ _ x, P%I) m) : bi_scope.

Notation "'[∧' 'map]' k ↦ x ∈ m , P" := (big_opM bi_and (λ k x, P) m) : bi_scope.
Notation "'[∧' 'map]' x ∈ m , P" := (big_opM bi_and (λ _ x, P) m) : bi_scope.

Notation "'[∗' 'set]' x ∈ X , P" := (big_opS bi_sep (λ x, P%I) X) : bi_scope.

Notation "'[∗' 'mset]' x ∈ X , P" := (big_opMS bi_sep (λ x, P%I) X) : bi_scope.

Definitions and notations for binary variants A version of the separating big operator that ranges over two lists. This version also ensures that both lists have the same length. Although this version can be defined in terms of the unary using a zip (see big_sepL2_alt), we do not define it that way to get better computational behavior (for simpl).
Fixpoint big_sepL2 {PROP : bi} {A B}
    (Φ : nat A B PROP) (l1 : list A) (l2 : list B) : PROP :=
  match l1, l2 with
  | [], []emp
  | x1 :: l1, x2 :: l2Φ 0 x1 x2 big_sepL2 (λ n, Φ (S n)) l1 l2
  | _, _False
  end%I.
Global Instance: Params (@big_sepL2) 3 := {}.
Global Arguments big_sepL2 {PROP A B} _ !_ !_ /.
Typeclasses Opaque big_sepL2.
Notation "'[∗' 'list]' k ↦ x1 ; x2 ∈ l1 ; l2 , P" :=
  (big_sepL2 (λ k x1 x2, P%I) l1 l2) : bi_scope.
Notation "'[∗' 'list]' x1 ; x2 ∈ l1 ; l2 , P" :=
  (big_sepL2 (λ _ x1 x2, P%I) l1 l2) : bi_scope.

Definition big_sepM2_def {PROP : bi} `{Countable K} {A B}
    (Φ : K A B PROP) (m1 : gmap K A) (m2 : gmap K B) : PROP :=
  ( k, is_Some (m1 !! k) is_Some (m2 !! k)
   [∗ map] k xy map_zip m1 m2, Φ k xy.1 xy.2)%I.
Definition big_sepM2_aux : seal (@big_sepM2_def). Proof. by eexists. Qed.
Definition big_sepM2 := big_sepM2_aux.(unseal).
Global Arguments big_sepM2 {PROP K _ _ A B} _ _ _.
Definition big_sepM2_eq : @big_sepM2 = _ := big_sepM2_aux.(seal_eq).
Global Instance: Params (@big_sepM2) 6 := {}.
Notation "'[∗' 'map]' k ↦ x1 ; x2 ∈ m1 ; m2 , P" :=
  (big_sepM2 (λ k x1 x2, P%I) m1 m2) : bi_scope.
Notation "'[∗' 'map]' x1 ; x2 ∈ m1 ; m2 , P" :=
  (big_sepM2 (λ _ x1 x2, P%I) m1 m2) : bi_scope.

Properties

Section big_op.
Context {PROP : bi}.
Implicit Types P Q : PROP.
Implicit Types Ps Qs : list PROP.
Implicit Types A : Type.

Big ops over lists

Section sep_list.
  Context {A : Type}.
  Implicit Types l : list A.
  Implicit Types Φ Ψ : nat A PROP.

  Lemma big_sepL_nil Φ : ([∗ list] ky nil, Φ k y) ⊣⊢ emp.
  Proof. done. Qed.
  Lemma big_sepL_nil' P `{!Affine P} Φ : P [∗ list] ky nil, Φ k y.
  Proof. apply: affine. Qed.
  Lemma big_sepL_cons Φ x l :
    ([∗ list] ky x :: l, Φ k y) ⊣⊢ Φ 0 x [∗ list] ky l, Φ (S k) y.
  Proof. by rewrite big_opL_cons. Qed.
  Lemma big_sepL_singleton Φ x : ([∗ list] ky [x], Φ k y) ⊣⊢ Φ 0 x.
  Proof. by rewrite big_opL_singleton. Qed.
  Lemma big_sepL_app Φ l1 l2 :
    ([∗ list] ky l1 ++ l2, Φ k y)
    ⊣⊢ ([∗ list] ky l1, Φ k y) ([∗ list] ky l2, Φ (length l1 + k) y).
  Proof. by rewrite big_opL_app. Qed.
  Lemma big_sepL_snoc Φ l x :
    ([∗ list] ky l ++ [x], Φ k y) ⊣⊢ ([∗ list] ky l, Φ k y) Φ (length l) x.
  Proof. by rewrite big_opL_snoc. Qed.

  Lemma big_sepL_take_drop Φ l n :
    ([∗ list] k x l, Φ k x) ⊣⊢
    ([∗ list] k x take n l, Φ k x) ([∗ list] k x drop n l, Φ (n + k) x).
  Proof. by rewrite big_opL_take_drop. Qed.

  Lemma big_sepL_submseteq (Φ : A PROP) `{!∀ x, Affine (Φ x)} l1 l2 :
    l1 ⊆+ l2 ([∗ list] y l2, Φ y) [∗ list] y l1, Φ y.
  Proof.
    intros [l ->]%submseteq_Permutation. rewrite big_sepL_app.
    induction l as [|x l IH]; simpl; [by rewrite right_id|by rewrite sep_elim_r].
  Qed.

The lemmas big_sepL_mono, big_sepL_ne and big_sepL_proper are more generic than the instances as they also give l !! k = Some y in the premise.
  Lemma big_sepL_mono Φ Ψ l :
    ( k y, l !! k = Some y Φ k y Ψ k y)
    ([∗ list] k y l, Φ k y) [∗ list] k y l, Ψ k y.
  Proof. apply big_opL_gen_proper; apply _. Qed.
  Lemma big_sepL_ne Φ Ψ l n :
    ( k y, l !! k = Some y Φ k y ≡{n}≡ Ψ k y)
    ([∗ list] k y l, Φ k y)%I ≡{n}≡ ([∗ list] k y l, Ψ k y)%I.
  Proof. apply big_opL_ne. Qed.
  Lemma big_sepL_proper Φ Ψ l :
    ( k y, l !! k = Some y Φ k y ⊣⊢ Ψ k y)
    ([∗ list] k y l, Φ k y) ⊣⊢ ([∗ list] k y l, Ψ k y).
  Proof. apply big_opL_proper. Qed.

No need to declare instances for non-expansiveness and properness, we get both from the generic big_opL instances.
  Global Instance big_sepL_mono' :
    Proper (pointwise_relation _ (pointwise_relation _ (⊢)) ==> (=) ==> (⊢))
           (big_opL (@bi_sep PROP) (A:=A)).
  Proof. intros f g Hf m ? <-. apply big_sepL_mono; intros; apply Hf. Qed.
  Global Instance big_sepL_id_mono' :
    Proper (Forall2 (⊢) ==> (⊢)) (big_opL (@bi_sep PROP) (λ _ P, P)).
  Proof. by induction 1 as [|P Q Ps Qs HPQ ? IH]; rewrite /= ?HPQ ?IH. Qed.

  Lemma big_sepL_emp l : ([∗ list] ky l, emp) ⊣⊢@{PROP} emp.
  Proof. by rewrite big_opL_unit. Qed.

  Lemma big_sepL_insert_acc Φ l i x :
    l !! i = Some x
    ([∗ list] ky l, Φ k y) Φ i x ( y, Φ i y -∗ ([∗ list] ky <[i:=y]>l, Φ k y)).
  Proof.
    intros Hli. assert (i length l) by eauto using lookup_lt_Some, Nat.lt_le_incl.
    rewrite -(take_drop_middle l i x) // big_sepL_app /=.
    rewrite Nat.add_0_r take_length_le //.
    rewrite assoc -!(comm _ (Φ _ _)) -assoc. apply sep_mono_r, forall_introy.
    rewrite insert_app_r_alt ?take_length_le //.
    rewrite Nat.sub_diag /=. apply wand_intro_l.
    rewrite assoc !(comm _ (Φ _ _)) -assoc big_sepL_app /=.
    by rewrite Nat.add_0_r take_length_le.
  Qed.

  Lemma big_sepL_lookup_acc Φ l i x :
    l !! i = Some x
    ([∗ list] ky l, Φ k y) Φ i x (Φ i x -∗ ([∗ list] ky l, Φ k y)).
  Proof. intros. by rewrite {1}big_sepL_insert_acc // (forall_elim x) list_insert_id. Qed.

  Lemma big_sepL_lookup Φ l i x `{!Absorbing (Φ i x)} :
    l !! i = Some x ([∗ list] ky l, Φ k y) Φ i x.
  Proof. intros. rewrite big_sepL_lookup_acc //. by rewrite sep_elim_l. Qed.

  Lemma big_sepL_elem_of (Φ : A PROP) l x `{!Absorbing (Φ x)} :
    x l ([∗ list] y l, Φ y) Φ x.
  Proof.
    intros [i ?]%elem_of_list_lookup. by eapply (big_sepL_lookup (λ _, Φ)).
  Qed.

  Lemma big_sepL_fmap {B} (f : A B) (Φ : nat B PROP) l :
    ([∗ list] ky f <$> l, Φ k y) ⊣⊢ ([∗ list] ky l, Φ k (f y)).
  Proof. by rewrite big_opL_fmap. Qed.

  Lemma big_sepL_omap {B} (f : A option B) (Φ : B PROP) l :
    ([∗ list] y omap f l, Φ y) ⊣⊢ ([∗ list] y l, from_option Φ emp (f y)).
  Proof. by rewrite big_opL_omap. Qed.

  Lemma big_sepL_bind {B} (f : A list B) (Φ : B PROP) l :
    ([∗ list] y l ≫= f, Φ y) ⊣⊢ ([∗ list] x l, [∗ list] y f x, Φ y).
  Proof. by rewrite big_opL_bind. Qed.

  Lemma big_sepL_sep Φ Ψ l :
    ([∗ list] kx l, Φ k x Ψ k x)
    ⊣⊢ ([∗ list] kx l, Φ k x) ([∗ list] kx l, Ψ k x).
  Proof. by rewrite big_opL_op. Qed.

  Lemma big_sepL_sep_2 Φ Ψ l :
    ([∗ list] kx l, Φ k x) -∗
    ([∗ list] kx l, Ψ k x) -∗
    ([∗ list] kx l, Φ k x Ψ k x).
  Proof. apply wand_intro_r. rewrite big_sepL_sep //. Qed.

  Lemma big_sepL_and Φ Ψ l :
    ([∗ list] kx l, Φ k x Ψ k x)
     ([∗ list] kx l, Φ k x) ([∗ list] kx l, Ψ k x).
  Proof. auto using and_intro, big_sepL_mono, and_elim_l, and_elim_r. Qed.

  Lemma big_sepL_pure_1 (φ : nat A Prop) l :
    ([∗ list] kx l, φ k x) ⊢@{PROP} k x, l !! k = Some x φ k x.
  Proof.
    induction l as [|x l IH] using rev_ind.
    { apply pure_intro=>??. rewrite lookup_nil. done. }
    rewrite big_sepL_snoc // IH sep_and -pure_and.
    f_equiv=>-[Hl Hx] k y /lookup_app_Some =>-[Hy|[Hlen Hy]].
    - by apply Hl.
    - apply list_lookup_singleton_Some in Hy as [Hk ->].
      replace k with (length l) by lia. done.
  Qed.
  Lemma big_sepL_affinely_pure_2 (φ : nat A Prop) l :
    <affine> k x, l !! k = Some x φ k x ⊢@{PROP} ([∗ list] kx l, <affine> φ k x).
  Proof.
    induction l as [|x l IH] using rev_ind.
    { rewrite big_sepL_nil. apply affinely_elim_emp. }
    rewrite big_sepL_snoc // -IH.
    rewrite -persistent_and_sep_1 -affinely_and -pure_and.
    f_equiv. f_equiv=>- Hlx. split.
    - intros k y Hy. apply Hlx. rewrite lookup_app Hy //.
    - apply Hlx. rewrite lookup_app lookup_ge_None_2 //.
      rewrite Nat.sub_diag //.
  Qed.
The general backwards direction requires BiAffine to cover the empty case.
  Lemma big_sepL_pure `{!BiAffine PROP} (φ : nat A Prop) l :
    ([∗ list] kx l, φ k x) ⊣⊢@{PROP} k x, l !! k = Some x φ k x.
  Proof.
    apply (anti_symm (⊢)); first by apply big_sepL_pure_1.
    rewrite -(affine_affinely _).
    rewrite big_sepL_affinely_pure_2. by setoid_rewrite affinely_elim.
  Qed.

  Lemma big_sepL_persistently `{BiAffine PROP} Φ l :
    <pers> ([∗ list] kx l, Φ k x) ⊣⊢ [∗ list] kx l, <pers> (Φ k x).
  Proof. apply (big_opL_commute _). Qed.

  Lemma big_sepL_intro Φ l :
     ( k x, l !! k = Some x Φ k x) [∗ list] kx l, Φ k x.
  Proof.
    revert Φ. induction l as [|x l IH]=> Φ /=; [by apply (affine _)|].
    rewrite intuitionistically_sep_dup. f_equiv.
    - rewrite (forall_elim 0) (forall_elim x) pure_True // True_impl.
      by rewrite intuitionistically_elim.
    - rewrite -IH. f_equiv.
      apply forall_introk; by rewrite (forall_elim (S k)).
  Qed.

  Lemma big_sepL_forall `{BiAffine PROP} Φ l :
    ( k x, Persistent (Φ k x))
    ([∗ list] kx l, Φ k x) ⊣⊢ ( k x, l !! k = Some x Φ k x).
  Proof.
    intros . apply (anti_symm _).
    { apply forall_introk; apply forall_introx.
      apply impl_intro_l, pure_elim_l⇒ ?; by apply: big_sepL_lookup. }
    rewrite -big_sepL_intro. setoid_rewrite pure_impl_forall.
    by rewrite intuitionistic_intuitionistically.
  Qed.

  Lemma big_sepL_impl Φ Ψ l :
    ([∗ list] kx l, Φ k x) -∗
     ( k x, l !! k = Some x Φ k x -∗ Ψ k x) -∗
    [∗ list] kx l, Ψ k x.
  Proof.
    apply wand_intro_l. rewrite big_sepL_intro -big_sepL_sep.
    by setoid_rewrite wand_elim_l.
  Qed.

  Lemma big_sepL_wand Φ Ψ l :
    ([∗ list] kx l, Φ k x) -∗
    ([∗ list] kx l, Φ k x -∗ Ψ k x) -∗
    [∗ list] kx l, Ψ k x.
  Proof.
    apply wand_intro_r. rewrite -big_sepL_sep.
    setoid_rewrite wand_elim_r. done.
  Qed.

  Lemma big_sepL_dup P `{!Affine P} l :
     (P -∗ P P) -∗ P -∗ [∗ list] kx l, P.
  Proof.
    apply wand_intro_l.
    induction l as [|x l IH]=> /=; first by apply: affine.
    rewrite intuitionistically_sep_dup {1}intuitionistically_elim.
    rewrite assoc wand_elim_r -assoc. apply sep_mono; done.
  Qed.

  Lemma big_sepL_delete Φ l i x :
    l !! i = Some x
    ([∗ list] ky l, Φ k y) ⊣⊢
    Φ i x [∗ list] ky l, if decide (k = i) then emp else Φ k y.
  Proof.
    intros. rewrite -(take_drop_middle l i x) // !big_sepL_app /= Nat.add_0_r.
    rewrite take_length_le; last eauto using lookup_lt_Some, Nat.lt_le_incl.
    rewrite decide_True // left_id.
    rewrite assoc -!(comm _ (Φ _ _)) -assoc. do 2 f_equiv.
    - apply big_sepL_properk y Hk. apply lookup_lt_Some in Hk.
      rewrite take_length in Hk. by rewrite decide_False; last lia.
    - apply big_sepL_properk y _. by rewrite decide_False; last lia.
  Qed.
  Lemma big_sepL_delete' `{!BiAffine PROP} Φ l i x :
    l !! i = Some x
    ([∗ list] ky l, Φ k y) ⊣⊢ Φ i x [∗ list] ky l, k i Φ k y.
  Proof.
    intros. rewrite big_sepL_delete //. (do 2 f_equiv)=> k y.
    rewrite -decide_emp. by repeat case_decide.
  Qed.

  Lemma big_sepL_lookup_acc_impl {Φ l} i x :
    l !! i = Some x
    ([∗ list] ky l, Φ k y) -∗
    
    Φ i x
    
     Ψ,
       ( k y, l !! k = Some y k i Φ k y -∗ Ψ k y) -∗
      Ψ i x -∗
      [∗ list] ky l, Ψ k y.
  Proof.
    intros. rewrite big_sepL_delete //. apply sep_mono_r, forall_introΨ.
    apply wand_intro_r, wand_intro_l.
    rewrite (big_sepL_delete Ψ l i x) //. apply sep_mono_r.
    eapply wand_apply; [apply big_sepL_impl|apply sep_mono_r].
    apply intuitionistically_intro', forall_introk; apply forall_introy.
    apply impl_intro_l, pure_elim_l⇒ ?; apply wand_intro_r.
    rewrite (forall_elim ) (forall_elim y) pure_True // left_id.
    destruct (decide _) as [->|]; [by apply: affine|].
    by rewrite pure_True //left_id intuitionistically_elim wand_elim_l.
  Qed.

  Lemma big_sepL_replicate l P :
    [∗] replicate (length l) P ⊣⊢ [∗ list] y l, P.
  Proof. induction l as [|x l]=> //=; by f_equiv. Qed.

  Lemma big_sepL_later `{BiAffine PROP} Φ l :
     ([∗ list] kx l, Φ k x) ⊣⊢ ([∗ list] kx l, Φ k x).
  Proof. apply (big_opL_commute _). Qed.
  Lemma big_sepL_later_2 Φ l :
    ([∗ list] kx l, Φ k x) [∗ list] kx l, Φ k x.
  Proof. by rewrite (big_opL_commute _). Qed.

  Lemma big_sepL_laterN `{BiAffine PROP} Φ n l :
    ▷^n ([∗ list] kx l, Φ k x) ⊣⊢ ([∗ list] kx l, ▷^n Φ k x).
  Proof. apply (big_opL_commute _). Qed.
  Lemma big_sepL_laterN_2 Φ n l :
    ([∗ list] kx l, ▷^n Φ k x) ▷^n [∗ list] kx l, Φ k x.
  Proof. by rewrite (big_opL_commute _). Qed.

  Global Instance big_sepL_nil_persistent Φ :
    Persistent ([∗ list] kx [], Φ k x).
  Proof. simpl; apply _. Qed.
  Global Instance big_sepL_persistent Φ l :
    ( k x, Persistent (Φ k x)) Persistent ([∗ list] kx l, Φ k x).
  Proof. revert Φ. induction l as [|x l IH]=> Φ ? /=; apply _. Qed.
  Global Instance big_sepL_persistent_id Ps :
    TCForall Persistent Ps Persistent ([∗] Ps).
  Proof. induction 1; simpl; apply _. Qed.

  Global Instance big_sepL_nil_affine Φ :
    Affine ([∗ list] kx [], Φ k x).
  Proof. simpl; apply _. Qed.
  Global Instance big_sepL_affine Φ l :
    ( k x, Affine (Φ k x)) Affine ([∗ list] kx l, Φ k x).
  Proof. revert Φ. induction l as [|x l IH]=> Φ ? /=; apply _. Qed.
  Global Instance big_sepL_affine_id Ps : TCForall Affine Ps Affine ([∗] Ps).
  Proof. induction 1; simpl; apply _. Qed.

  Global Instance big_sepL_nil_timeless `{!Timeless (emp%I : PROP)} Φ :
    Timeless ([∗ list] kx [], Φ k x).
  Proof. simpl; apply _. Qed.
  Global Instance big_sepL_timeless `{!Timeless (emp%I : PROP)} Φ l :
    ( k x, Timeless (Φ k x)) Timeless ([∗ list] kx l, Φ k x).
  Proof. revert Φ. induction l as [|x l IH]=> Φ ? /=; apply _. Qed.
  Global Instance big_sepL_timeless_id `{!Timeless (emp%I : PROP)} Ps :
    TCForall Timeless Ps Timeless ([∗] Ps).
  Proof. induction 1; simpl; apply _. Qed.
End sep_list.

Lemma big_sepL_sep_zip_with {A B C} (f : A B C) (g1 : C A) (g2 : C B)
    (Φ1 : nat A PROP) (Φ2 : nat B PROP) l1 l2 :
  ( x y, g1 (f x y) = x)
  ( x y, g2 (f x y) = y)
  length l1 = length l2
  ([∗ list] kxy zip_with f l1 l2, Φ1 k (g1 xy) Φ2 k (g2 xy)) ⊣⊢
  ([∗ list] kx l1, Φ1 k x) ([∗ list] ky l2, Φ2 k y).
Proof. apply big_opL_sep_zip_with. Qed.

Lemma big_sepL_sep_zip {A B} (Φ1 : nat A PROP) (Φ2 : nat B PROP) l1 l2 :
  length l1 = length l2
  ([∗ list] kxy zip l1 l2, Φ1 k xy.1 Φ2 k xy.2) ⊣⊢
  ([∗ list] kx l1, Φ1 k x) ([∗ list] ky l2, Φ2 k y).
Proof. apply big_opL_sep_zip. Qed.

Lemma big_sepL_zip_with {A B C} (Φ : nat A PROP) f (l1 : list B) (l2 : list C) :
  ([∗ list] kx zip_with f l1 l2, Φ k x) ⊣⊢
  ([∗ list] kx l1, if l2 !! k is Some y then Φ k (f x y) else emp).
Proof.
  revert Φ l2; induction l1 as [|x l1 IH]=> Φ [|y l2] //=.
  - by rewrite big_sepL_emp left_id.
  - by rewrite IH.
Qed.

Big ops over two lists

Lemma big_sepL2_alt {A B} (Φ : nat A B PROP) l1 l2 :
  ([∗ list] ky1;y2 l1; l2, Φ k y1 y2) ⊣⊢
   length l1 = length l2 [∗ list] k xy zip l1 l2, Φ k (xy.1) (xy.2).
Proof.
  apply (anti_symm _).
  - apply and_intro.
    + revert Φ l2. induction l1 as [|x1 l1 IH]=> Φ -[|x2 l2] /=;
        auto using pure_intro, False_elim.
      rewrite IH sep_elim_r. apply pure_mono; auto.
    + revert Φ l2. induction l1 as [|x1 l1 IH]=> Φ -[|x2 l2] /=;
        auto using pure_intro, False_elim.
      by rewrite IH.
  - apply pure_elim_l⇒ /Forall2_same_length Hl. revert Φ.
    induction Hl as [|x1 l1 x2 l2 _ _ IH]=> Φ //=. by rewrite -IH.
Qed.

Section sep_list2.
  Context {A B : Type}.
  Implicit Types Φ Ψ : nat A B PROP.

  Lemma big_sepL2_nil Φ : ([∗ list] ky1;y2 []; [], Φ k y1 y2) ⊣⊢ emp.
  Proof. done. Qed.
  Lemma big_sepL2_nil' P `{!Affine P} Φ : P [∗ list] ky1;y2 [];[], Φ k y1 y2.
  Proof. apply: affine. Qed.
  Lemma big_sepL2_nil_inv_l Φ l2 :
    ([∗ list] ky1;y2 []; l2, Φ k y1 y2) -∗ l2 = [].
  Proof. destruct l2; simpl; auto using False_elim, pure_intro. Qed.
  Lemma big_sepL2_nil_inv_r Φ l1 :
    ([∗ list] ky1;y2 l1; [], Φ k y1 y2) -∗ l1 = [].
  Proof. destruct l1; simpl; auto using False_elim, pure_intro. Qed.

  Lemma big_sepL2_cons Φ x1 x2 l1 l2 :
    ([∗ list] ky1;y2 x1 :: l1; x2 :: l2, Φ k y1 y2)
    ⊣⊢ Φ 0 x1 x2 [∗ list] ky1;y2 l1;l2, Φ (S k) y1 y2.
  Proof. done. Qed.
  Lemma big_sepL2_cons_inv_l Φ x1 l1 l2 :
    ([∗ list] ky1;y2 x1 :: l1; l2, Φ k y1 y2) -∗
     x2 l2', l2 = x2 :: l2'
              Φ 0 x1 x2 [∗ list] ky1;y2 l1;l2', Φ (S k) y1 y2.
  Proof.
    destruct l2 as [|x2 l2]; simpl; auto using False_elim.
    by rewrite -(exist_intro x2) -(exist_intro l2) pure_True // left_id.
  Qed.
  Lemma big_sepL2_cons_inv_r Φ x2 l1 l2 :
    ([∗ list] ky1;y2 l1; x2 :: l2, Φ k y1 y2) -∗
     x1 l1', l1 = x1 :: l1'
              Φ 0 x1 x2 [∗ list] ky1;y2 l1';l2, Φ (S k) y1 y2.
  Proof.
    destruct l1 as [|x1 l1]; simpl; auto using False_elim.
    by rewrite -(exist_intro x1) -(exist_intro l1) pure_True // left_id.
  Qed.

  Lemma big_sepL2_singleton Φ x1 x2 :
    ([∗ list] ky1;y2 [x1];[x2], Φ k y1 y2) ⊣⊢ Φ 0 x1 x2.
  Proof. by rewrite /= right_id. Qed.

  Lemma big_sepL2_length Φ l1 l2 :
    ([∗ list] ky1;y2 l1; l2, Φ k y1 y2) -∗ length l1 = length l2 .
  Proof. by rewrite big_sepL2_alt and_elim_l. Qed.

  Lemma big_sepL2_app Φ l1 l2 l1' l2' :
    ([∗ list] ky1;y2 l1; l1', Φ k y1 y2) -∗
    ([∗ list] ky1;y2 l2; l2', Φ (length l1 + k) y1 y2) -∗
    ([∗ list] ky1;y2 l1 ++ l2; l1' ++ l2', Φ k y1 y2).
  Proof.
    apply wand_intro_r. revert Φ l1'. induction l1 as [|x1 l1 IH]=> Φ -[|x1' l1'] /=.
    - by rewrite left_id.
    - rewrite left_absorb. apply False_elim.
    - rewrite left_absorb. apply False_elim.
    - by rewrite -assoc IH.
  Qed.
  Lemma big_sepL2_app_inv_l Φ l1' l1'' l2 :
    ([∗ list] ky1;y2 l1' ++ l1''; l2, Φ k y1 y2) -∗
     l2' l2'', l2 = l2' ++ l2''
                ([∗ list] ky1;y2 l1';l2', Φ k y1 y2)
                ([∗ list] ky1;y2 l1'';l2'', Φ (length l1' + k) y1 y2).
  Proof.
    rewrite -(exist_intro (take (length l1') l2))
      -(exist_intro (drop (length l1') l2)) take_drop pure_True // left_id.
    revert Φ l2. induction l1' as [|x1 l1' IH]=> Φ -[|x2 l2] /=;
       [by rewrite left_id|by rewrite left_id|apply False_elim|].
    by rewrite IH -assoc.
  Qed.
  Lemma big_sepL2_app_inv_r Φ l1 l2' l2'' :
    ([∗ list] ky1;y2 l1; l2' ++ l2'', Φ k y1 y2) -∗
     l1' l1'', l1 = l1' ++ l1''
                ([∗ list] ky1;y2 l1';l2', Φ k y1 y2)
                ([∗ list] ky1;y2 l1'';l2'', Φ (length l2' + k) y1 y2).
  Proof.
    rewrite -(exist_intro (take (length l2') l1))
      -(exist_intro (drop (length l2') l1)) take_drop pure_True // left_id.
    revert Φ l1. induction l2' as [|x2 l2' IH]=> Φ -[|x1 l1] /=;
       [by rewrite left_id|by rewrite left_id|apply False_elim|].
    by rewrite IH -assoc.
  Qed.
  Lemma big_sepL2_app_inv Φ l1 l2 l1' l2' :
    length l1 = length l1' length l2 = length l2'
    ([∗ list] ky1;y2 l1 ++ l2; l1' ++ l2', Φ k y1 y2) -∗
    ([∗ list] ky1;y2 l1; l1', Φ k y1 y2)
    ([∗ list] ky1;y2 l2; l2', Φ (length l1 + k)%nat y1 y2).
  Proof.
    revert Φ l1'. induction l1 as [|x1 l1 IH]=> Φ -[|x1' l1'] /= Hlen.
    - by rewrite left_id.
    - destruct Hlen as [[=]|Hlen]. rewrite big_sepL2_length Hlen /= app_length.
      apply pure_elim'; lia.
    - destruct Hlen as [[=]|Hlen]. rewrite big_sepL2_length -Hlen /= app_length.
      apply pure_elim'; lia.
    - by rewrite -assoc IH; last lia.
  Qed.
  Lemma big_sepL2_app_same_length Φ l1 l2 l1' l2' :
    length l1 = length l1' length l2 = length l2'
    ([∗ list] ky1;y2 l1 ++ l2; l1' ++ l2', Φ k y1 y2) ⊣⊢
    ([∗ list] ky1;y2 l1; l1', Φ k y1 y2)
    ([∗ list] ky1;y2 l2; l2', Φ (length l1 + k)%nat y1 y2).
  Proof.
    intros. apply (anti_symm _).
    - by apply big_sepL2_app_inv.
    - apply wand_elim_l'. apply big_sepL2_app.
  Qed.

  Lemma big_sepL2_snoc Φ x1 x2 l1 l2 :
    ([∗ list] ky1;y2 l1 ++ [x1]; l2 ++ [x2], Φ k y1 y2) ⊣⊢
    ([∗ list] ky1;y2 l1; l2, Φ k y1 y2) Φ (length l1) x1 x2.
  Proof.
    rewrite big_sepL2_app_same_length; last by auto.
    by rewrite big_sepL2_singleton Nat.add_0_r.
  Qed.

The lemmas big_sepL2_mono, big_sepL2_ne and big_sepL2_proper are more generic than the instances as they also give li !! k = Some yi in the premise.
  Lemma big_sepL2_mono Φ Ψ l1 l2 :
    ( k y1 y2, l1 !! k = Some y1 l2 !! k = Some y2 Φ k y1 y2 Ψ k y1 y2)
    ([∗ list] k y1;y2 l1;l2, Φ k y1 y2) [∗ list] k y1;y2 l1;l2, Ψ k y1 y2.
  Proof.
    intros H. rewrite !big_sepL2_alt. f_equiv. apply big_sepL_monok [y1 y2].
    rewrite lookup_zip_with⇒ ?; simplify_option_eq; auto.
  Qed.
  Lemma big_sepL2_ne Φ Ψ l1 l2 n :
    ( k y1 y2, l1 !! k = Some y1 l2 !! k = Some y2 Φ k y1 y2 ≡{n}≡ Ψ k y1 y2)
    ([∗ list] k y1;y2 l1;l2, Φ k y1 y2)%I ≡{n}≡ ([∗ list] k y1;y2 l1;l2, Ψ k y1 y2)%I.
  Proof.
    intros H. rewrite !big_sepL2_alt. f_equiv. apply big_sepL_nek [y1 y2].
    rewrite lookup_zip_with⇒ ?; simplify_option_eq; auto.
  Qed.
  Lemma big_sepL2_proper Φ Ψ l1 l2 :
    ( k y1 y2, l1 !! k = Some y1 l2 !! k = Some y2 Φ k y1 y2 ⊣⊢ Ψ k y1 y2)
    ([∗ list] k y1;y2 l1;l2, Φ k y1 y2) ⊣⊢ [∗ list] k y1;y2 l1;l2, Ψ k y1 y2.
  Proof.
    intros; apply (anti_symm _);
      apply big_sepL2_mono; auto using equiv_entails_1_1, equiv_entails_1_2.
  Qed.
  Lemma big_sepL2_proper_2 `{!Equiv A, !Equiv B} Φ Ψ l1 l2 l1' l2' :
    l1 l1' l2 l2'
    ( k y1 y1' y2 y2',
      l1 !! k = Some y1 l1' !! k = Some y1' y1 y1'
      l2 !! k = Some y2 l2' !! k = Some y2' y2 y2'
      Φ k y1 y2 ⊣⊢ Ψ k y1' y2')
    ([∗ list] k y1;y2 l1;l2, Φ k y1 y2) ⊣⊢ [∗ list] k y1;y2 l1';l2', Ψ k y1 y2.
  Proof.
    intros Hl1 Hl2 Hf. rewrite !big_sepL2_alt. f_equiv.
    { do 2 f_equiv; by apply length_proper. }
    apply big_opL_proper_2; [by f_equiv|].
    intros k [x1 y1] [x2 y2] (?&?&[=<- <-]&?&?)%lookup_zip_with_Some
      (?&?&[=<- <-]&?&?)%lookup_zip_with_Some [??]; naive_solver.
  Qed.

  Global Instance big_sepL2_ne' n :
    Proper (pointwise_relation _ (pointwise_relation _ (pointwise_relation _ (dist n)))
      ==> (=) ==> (=) ==> (dist n))
           (big_sepL2 (PROP:=PROP) (A:=A) (B:=B)).
  Proof. intros f g Hf l1 ? <- l2 ? <-. apply big_sepL2_ne; intros; apply Hf. Qed.
  Global Instance big_sepL2_mono' :
    Proper (pointwise_relation _ (pointwise_relation _ (pointwise_relation _ (⊢)))
      ==> (=) ==> (=) ==> (⊢))
           (big_sepL2 (PROP:=PROP) (A:=A) (B:=B)).
  Proof. intros f g Hf l1 ? <- l2 ? <-. apply big_sepL2_mono; intros; apply Hf. Qed.
  Global Instance big_sepL2_proper' :
    Proper (pointwise_relation _ (pointwise_relation _ (pointwise_relation _ (⊣⊢)))
      ==> (=) ==> (=) ==> (⊣⊢))
           (big_sepL2 (PROP:=PROP) (A:=A) (B:=B)).
  Proof. intros f g Hf l1 ? <- l2 ? <-. apply big_sepL2_proper; intros; apply Hf. Qed.

  Lemma big_sepL2_insert_acc Φ l1 l2 i x1 x2 :
    l1 !! i = Some x1 l2 !! i = Some x2
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2)
    Φ i x1 x2 ( y1 y2, Φ i y1 y2 -∗ ([∗ list] ky1;y2 <[i:=y1]>l1;<[i:=y2]>l2, Φ k y1 y2)).
  Proof.
    intros Hl1 Hl2. rewrite big_sepL2_alt. apply pure_elim_lHl.
    rewrite {1}big_sepL_insert_acc; last by rewrite lookup_zip_with; simplify_option_eq.
    apply sep_mono_r. apply forall_introy1. apply forall_introy2.
    rewrite big_sepL2_alt !insert_length pure_True // left_id -insert_zip_with.
    by rewrite (forall_elim (y1, y2)).
  Qed.

  Lemma big_sepL2_lookup_acc Φ l1 l2 i x1 x2 :
    l1 !! i = Some x1 l2 !! i = Some x2
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2)
    Φ i x1 x2 (Φ i x1 x2 -∗ ([∗ list] ky1;y2 l1;l2, Φ k y1 y2)).
  Proof.
    intros. rewrite {1}big_sepL2_insert_acc // (forall_elim x1) (forall_elim x2).
    by rewrite !list_insert_id.
  Qed.

  Lemma big_sepL2_lookup Φ l1 l2 i x1 x2 `{!Absorbing (Φ i x1 x2)} :
    l1 !! i = Some x1 l2 !! i = Some x2
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) Φ i x1 x2.
  Proof. intros. rewrite big_sepL2_lookup_acc //. by rewrite sep_elim_l. Qed.

  Lemma big_sepL2_fmap_l {A'} (f : A A') (Φ : nat A' B PROP) l1 l2 :
    ([∗ list] ky1;y2 f <$> l1; l2, Φ k y1 y2)
    ⊣⊢ ([∗ list] ky1;y2 l1;l2, Φ k (f y1) y2).
  Proof.
    rewrite !big_sepL2_alt fmap_length zip_with_fmap_l zip_with_zip big_sepL_fmap.
    by f_equiv; f_equivk [??].
  Qed.
  Lemma big_sepL2_fmap_r {B'} (g : B B') (Φ : nat A B' PROP) l1 l2 :
    ([∗ list] ky1;y2 l1; g <$> l2, Φ k y1 y2)
    ⊣⊢ ([∗ list] ky1;y2 l1;l2, Φ k y1 (g y2)).
  Proof.
    rewrite !big_sepL2_alt fmap_length zip_with_fmap_r zip_with_zip big_sepL_fmap.
    by f_equiv; f_equivk [??].
  Qed.

  Lemma big_sepL2_reverse_2 (Φ : A B PROP) l1 l2 :
    ([∗ list] y1;y2 l1;l2, Φ y1 y2) ([∗ list] y1;y2 reverse l1;reverse l2, Φ y1 y2).
  Proof.
    revert l2. induction l1 as [|x1 l1 IH]; intros [|x2 l2]; simpl; auto using False_elim.
    rewrite !reverse_cons (comm bi_sep) IH.
    by rewrite (big_sepL2_app _ _ [x1] _ [x2]) big_sepL2_singleton wand_elim_l.
  Qed.
  Lemma big_sepL2_reverse (Φ : A B PROP) l1 l2 :
    ([∗ list] y1;y2 reverse l1;reverse l2, Φ y1 y2) ⊣⊢ ([∗ list] y1;y2 l1;l2, Φ y1 y2).
  Proof. apply (anti_symm _); by rewrite big_sepL2_reverse_2 ?reverse_involutive. Qed.

  Lemma big_sepL2_replicate_l l x Φ n :
    length l = n
    ([∗ list] kx1;x2 replicate n x; l, Φ k x1 x2) ⊣⊢ [∗ list] kx2 l, Φ k x x2.
  Proof. intros <-. revert Φ. induction l as [|y l IH]=> //= Φ. by rewrite IH. Qed.
  Lemma big_sepL2_replicate_r l x Φ n :
    length l = n
    ([∗ list] kx1;x2 l;replicate n x, Φ k x1 x2) ⊣⊢ [∗ list] kx1 l, Φ k x1 x.
  Proof. intros <-. revert Φ. induction l as [|y l IH]=> //= Φ. by rewrite IH. Qed.

  Lemma big_sepL2_sep Φ Ψ l1 l2 :
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2 Ψ k y1 y2)
    ⊣⊢ ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) ([∗ list] ky1;y2 l1;l2, Ψ k y1 y2).
  Proof.
    rewrite !big_sepL2_alt big_sepL_sep !persistent_and_affinely_sep_l.
    rewrite -assoc (assoc _ _ (<affine> _)%I). rewrite -(comm bi_sep (<affine> _)%I).
    rewrite -assoc (assoc _ _ (<affine> _)%I) -!persistent_and_affinely_sep_l.
    by rewrite affinely_and_r persistent_and_affinely_sep_l idemp.
  Qed.

  Lemma big_sepL2_sep_2 Φ Ψ l1 l2 :
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) -∗
    ([∗ list] ky1;y2 l1;l2, Ψ k y1 y2) -∗
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2 Ψ k y1 y2).
  Proof. apply wand_intro_r. rewrite big_sepL2_sep //. Qed.

  Lemma big_sepL2_and Φ Ψ l1 l2 :
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2 Ψ k y1 y2)
     ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) ([∗ list] ky1;y2 l1;l2, Ψ k y1 y2).
  Proof. auto using and_intro, big_sepL2_mono, and_elim_l, and_elim_r. Qed.

  Lemma big_sepL2_pure_1 (φ : nat A B Prop) l1 l2 :
    ([∗ list] ky1;y2 l1;l2, φ k y1 y2) ⊢@{PROP}
       k y1 y2, l1 !! k = Some y1 l2 !! k = Some y2 φ k y1 y2.
  Proof.
    rewrite big_sepL2_alt big_sepL_pure_1.
    rewrite -pure_and. f_equiv=>-[Hlen Hlookup] k y1 y2 Hy1 Hy2.
    eapply (Hlookup k (y1, y2)).
    rewrite lookup_zip_with Hy1 /= Hy2 /= //.
  Qed.
  Lemma big_sepL2_affinely_pure_2 (φ : nat A B Prop) l1 l2 :
    length l1 = length l2
    <affine> k y1 y2, l1 !! k = Some y1 l2 !! k = Some y2 φ k y1 y2 ⊢@{PROP}
    ([∗ list] ky1;y2 l1;l2, <affine> φ k y1 y2).
  Proof.
    intros Hdom. rewrite big_sepL2_alt.
    rewrite -big_sepL_affinely_pure_2.
    rewrite affinely_and_r -pure_and. f_equiv. f_equiv=>-Hforall.
    split; first done.
    intros k [y1 y2] (? & ? & [= <- <-] & Hy1 & Hy2)%lookup_zip_with_Some.
    by eapply Hforall.
  Qed.
The general backwards direction requires BiAffine to cover the empty case.
  Lemma big_sepL2_pure `{!BiAffine PROP} (φ : nat A B Prop) l1 l2 :
    ([∗ list] ky1;y2 l1;l2, φ k y1 y2) ⊣⊢@{PROP}
      length l1 = length l2
        k y1 y2, l1 !! k = Some y1 l2 !! k = Some y2 φ k y1 y2.
  Proof.
    apply (anti_symm (⊢)).
    { rewrite pure_and. apply and_intro.
      - apply big_sepL2_length.
      - apply big_sepL2_pure_1. }
    rewrite -(affine_affinely _%I).
    rewrite pure_and -affinely_and_r.
    apply pure_elim_lHdom.
    rewrite big_sepL2_affinely_pure_2 //. by setoid_rewrite affinely_elim.
  Qed.

  Lemma big_sepL2_persistently `{BiAffine PROP} Φ l1 l2 :
    <pers> ([∗ list] ky1;y2 l1;l2, Φ k y1 y2)
    ⊣⊢ [∗ list] ky1;y2 l1;l2, <pers> (Φ k y1 y2).
  Proof.
    by rewrite !big_sepL2_alt persistently_and persistently_pure big_sepL_persistently.
  Qed.

  Lemma big_sepL2_intro Φ l1 l2 :
    length l1 = length l2
     ( k x1 x2, l1 !! k = Some x1 l2 !! k = Some x2 Φ k x1 x2)
    [∗ list] kx1;x2 l1;l2, Φ k x1 x2.
  Proof.
    revert l2 Φ. induction l1 as [|x1 l1 IH]=> -[|x2 l2] Φ ?; simplify_eq/=.
    { by apply (affine _). }
    rewrite intuitionistically_sep_dup. f_equiv.
    - rewrite (forall_elim 0) (forall_elim x1) (forall_elim x2).
      by rewrite !pure_True // !True_impl intuitionistically_elim.
    - rewrite -IH //. f_equiv.
      by apply forall_introk; by rewrite (forall_elim (S k)).
  Qed.

  Lemma big_sepL2_forall `{BiAffine PROP} Φ l1 l2 :
    ( k x1 x2, Persistent (Φ k x1 x2))
    ([∗ list] kx1;x2 l1;l2, Φ k x1 x2) ⊣⊢
      length l1 = length l2
       ( k x1 x2, l1 !! k = Some x1 l2 !! k = Some x2 Φ k x1 x2).
  Proof.
    intros. apply (anti_symm _).
    - apply and_intro; [apply big_sepL2_length|].
      apply forall_introk. apply forall_introx1. apply forall_introx2.
      do 2 (apply impl_intro_l; apply pure_elim_l⇒ ?). by apply :big_sepL2_lookup.
    - apply pure_elim_l⇒ ?. rewrite -big_sepL2_intro //.
      repeat setoid_rewrite pure_impl_forall.
      by rewrite intuitionistic_intuitionistically.
  Qed.

  Lemma big_sepL2_impl Φ Ψ l1 l2 :
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) -∗
     ( k x1 x2,
      l1 !! k = Some x1 l2 !! k = Some x2 Φ k x1 x2 -∗ Ψ k x1 x2) -∗
    [∗ list] ky1;y2 l1;l2, Ψ k y1 y2.
  Proof.
    rewrite -(idemp bi_and (big_sepL2 _ _ _)) {1}big_sepL2_length.
    apply pure_elim_l⇒ ?. rewrite big_sepL2_intro //.
    apply bi.wand_intro_l. rewrite -big_sepL2_sep. by setoid_rewrite wand_elim_l.
  Qed.

  Lemma big_sepL2_wand Φ Ψ l1 l2 :
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) -∗
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2 -∗ Ψ k y1 y2) -∗
    [∗ list] ky1;y2 l1;l2, Ψ k y1 y2.
  Proof.
    apply wand_intro_r. rewrite -big_sepL2_sep.
    setoid_rewrite wand_elim_r. done.
  Qed.

  Lemma big_sepL2_delete Φ l1 l2 i x1 x2 :
    l1 !! i = Some x1 l2 !! i = Some x2
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) ⊣⊢
    Φ i x1 x2 [∗ list] ky1;y2 l1;l2, if decide (k = i) then emp else Φ k y1 y2.
  Proof.
    intros. rewrite -(take_drop_middle l1 i x1) // -(take_drop_middle l2 i x2) //.
    assert (i < length l1 i < length l2) as [??] by eauto using lookup_lt_Some.
    rewrite !big_sepL2_app_same_length /=; [|rewrite ?take_length; lia..].
    rewrite Nat.add_0_r take_length_le; [|lia].
    rewrite decide_True // left_id.
    rewrite assoc -!(comm _ (Φ _ _ _)) -assoc. do 2 f_equiv.
    - apply big_sepL2_properk y1 y2 Hk. apply lookup_lt_Some in Hk.
      rewrite take_length in Hk. by rewrite decide_False; last lia.
    - apply big_sepL2_properk y1 y2 _. by rewrite decide_False; last lia.
  Qed.
  Lemma big_sepL2_delete' `{!BiAffine PROP} Φ l1 l2 i x1 x2 :
    l1 !! i = Some x1 l2 !! i = Some x2
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) ⊣⊢
    Φ i x1 x2 [∗ list] ky1;y2 l1;l2, k i Φ k y1 y2.
  Proof.
    intros. rewrite big_sepL2_delete //. (do 2 f_equiv)=> k y1 y2.
    rewrite -decide_emp. by repeat case_decide.
  Qed.

  Lemma big_sepL2_lookup_acc_impl {Φ l1 l2} i x1 x2 :
    l1 !! i = Some x1
    l2 !! i = Some x2
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) -∗
    
    Φ i x1 x2
    
     Ψ,
       ( k y1 y2,
         l1 !! k = Some y1 l2 !! k = Some y2 k i
        Φ k y1 y2 -∗ Ψ k y1 y2) -∗
      Ψ i x1 x2 -∗
      [∗ list] ky1;y2 l1;l2, Ψ k y1 y2.
  Proof.
    intros. rewrite big_sepL2_delete //. apply sep_mono_r, forall_introΨ.
    apply wand_intro_r, wand_intro_l.
    rewrite (big_sepL2_delete Ψ l1 l2 i) //. apply sep_mono_r.
    eapply wand_apply; [apply big_sepL2_impl|apply sep_mono_r].
    apply intuitionistically_intro', forall_introk;
      apply forall_introy1; apply forall_introy2.
    do 2 (apply impl_intro_l, pure_elim_l⇒ ?); apply wand_intro_r.
    rewrite (forall_elim k) (forall_elim y1) (forall_elim y2).
    rewrite !(pure_True (_ = Some _)) // !left_id.
    destruct (decide _) as [->|]; [by apply: affine|].
    by rewrite pure_True //left_id intuitionistically_elim wand_elim_l.
  Qed.

  Lemma big_sepL2_later_1 `{BiAffine PROP} Φ l1 l2 :
    ( [∗ list] ky1;y2 l1;l2, Φ k y1 y2) [∗ list] ky1;y2 l1;l2, Φ k y1 y2.
  Proof.
    rewrite !big_sepL2_alt later_and big_sepL_later (timeless _ ).
    rewrite except_0_and. auto using and_mono, except_0_intro.
  Qed.

  Lemma big_sepL2_later_2 Φ l1 l2 :
    ([∗ list] ky1;y2 l1;l2, Φ k y1 y2) [∗ list] ky1;y2 l1;l2, Φ k y1 y2.
  Proof.
    rewrite !big_sepL2_alt later_and big_sepL_later_2.
    auto using and_mono, later_intro.
  Qed.

  Lemma big_sepL2_laterN_2 Φ n l1 l2 :
    ([∗ list] ky1;y2 l1;l2, ▷^n Φ k y1 y2) ▷^n [∗ list] ky1;y2 l1;l2, Φ k y1 y2.
  Proof.
    rewrite !big_sepL2_alt laterN_and big_sepL_laterN_2.
    auto using and_mono, laterN_intro.
  Qed.

  Lemma big_sepL2_flip Φ l1 l2 :
    ([∗ list] ky1;y2 l2; l1, Φ k y2 y1) ⊣⊢ ([∗ list] ky1;y2 l1; l2, Φ k y1 y2).
  Proof.
    revert Φ l2. induction l1 as [|x1 l1 IH]=> Φ -[|x2 l2]//=; simplify_eq.
    by rewrite IH.
  Qed.

  Lemma big_sepL2_sepL (Φ1 : nat A PROP) (Φ2 : nat B PROP) l1 l2 :
    length l1 = length l2
    ([∗ list] ky1;y2 l1;l2, Φ1 k y1 Φ2 k y2) ⊣⊢
    ([∗ list] ky1 l1, Φ1 k y1) ([∗ list] ky2 l2, Φ2 k y2).
  Proof.
    intros. rewrite -big_sepL_sep_zip // big_sepL2_alt pure_True // left_id //.
  Qed.
  Lemma big_sepL2_sepL_2 (Φ1 : nat A PROP) (Φ2 : nat B PROP) l1 l2 :
    length l1 = length l2
    ([∗ list] ky1 l1, Φ1 k y1) -∗
    ([∗ list] ky2 l2, Φ2 k y2) -∗
    [∗ list] ky1;y2 l1;l2, Φ1 k y1 Φ2 k y2.
  Proof. intros. apply wand_intro_r. by rewrite big_sepL2_sepL. Qed.

  Global Instance big_sepL2_nil_persistent Φ :
    Persistent ([∗ list] ky1;y2 []; [], Φ k y1 y2).
  Proof. simpl; apply _. Qed.
  Global Instance big_sepL2_persistent Φ l1 l2 :
    ( k x1 x2, Persistent (Φ k x1 x2))
    Persistent ([∗ list] ky1;y2 l1;l2, Φ k y1 y2).
  Proof. rewrite big_sepL2_alt. apply _. Qed.

  Global Instance big_sepL2_nil_affine Φ :
    Affine ([∗ list] ky1;y2 []; [], Φ k y1 y2).
  Proof. simpl; apply _. Qed.
  Global Instance big_sepL2_affine Φ l1 l2 :
    ( k x1 x2, Affine (Φ k x1 x2))
    Affine ([∗ list] ky1;y2 l1;l2, Φ k y1 y2).
  Proof. rewrite big_sepL2_alt. apply _. Qed.

  Global Instance big_sepL2_nil_timeless `{!Timeless (emp%I : PROP)} Φ :
    Timeless ([∗ list] ky1;y2 []; [], Φ k y1 y2).
  Proof. simpl; apply _. Qed.
  Global Instance big_sepL2_timeless `{!Timeless (emp%I : PROP)} Φ l1 l2 :
    ( k x1 x2, Timeless (Φ k x1 x2))
    Timeless ([∗ list] ky1;y2 l1;l2, Φ k y1 y2).
  Proof. rewrite big_sepL2_alt. apply _. Qed.
End sep_list2.

Lemma big_sepL_sepL2_diag {A} (Φ : nat A A PROP) (l : list A) :
  ([∗ list] ky l, Φ k y y) -∗
  ([∗ list] ky1;y2 l;l, Φ k y1 y2).
Proof.
  rewrite big_sepL2_alt. rewrite pure_True // left_id.
  rewrite zip_diag big_sepL_fmap /=. done.
Qed.

Lemma big_sepL2_ne_2 {A B : ofe}
    (Φ Ψ : nat A B PROP) l1 l2 l1' l2' n :
  l1 ≡{n}≡ l1' l2 ≡{n}≡ l2'
  ( k y1 y1' y2 y2',
    l1 !! k = Some y1 l1' !! k = Some y1' y1 ≡{n}≡ y1'
    l2 !! k = Some y2 l2' !! k = Some y2' y2 ≡{n}≡ y2'
    Φ k y1 y2 ≡{n}≡ Ψ k y1' y2')
  ([∗ list] k y1;y2 l1;l2, Φ k y1 y2)%I ≡{n}≡ ([∗ list] k y1;y2 l1';l2', Ψ k y1 y2)%I.
Proof.
  intros Hl1 Hl2 Hf. rewrite !big_sepL2_alt. f_equiv.
  { do 2 f_equiv; by apply: length_ne. }
  apply big_opL_ne_2; [by f_equiv|].
  intros k [x1 y1] [x2 y2] (?&?&[=<- <-]&?&?)%lookup_zip_with_Some
    (?&?&[=<- <-]&?&?)%lookup_zip_with_Some [??]; naive_solver.
Qed.

Section and_list.
  Context {A : Type}.
  Implicit Types l : list A.
  Implicit Types Φ Ψ : nat A PROP.

  Lemma big_andL_nil Φ : ([∧ list] ky nil, Φ k y) ⊣⊢ True.
  Proof. done. Qed.
  Lemma big_andL_nil' P Φ : P [∧ list] ky nil, Φ k y.
  Proof. by apply pure_intro. Qed.
  Lemma big_andL_cons Φ x l :
    ([∧ list] ky x :: l, Φ k y) ⊣⊢ Φ 0 x [∧ list] ky l, Φ (S k) y.
  Proof. by rewrite big_opL_cons. Qed.
  Lemma big_andL_singleton Φ x : ([∧ list] ky [x], Φ k y) ⊣⊢ Φ 0 x.
  Proof. by rewrite big_opL_singleton. Qed.
  Lemma big_andL_app Φ l1 l2 :
    ([∧ list] ky l1 ++ l2, Φ k y)
    ⊣⊢ ([∧ list] ky l1, Φ k y) ([∧ list] ky l2, Φ (length l1 + k) y).
  Proof. by rewrite big_opL_app. Qed.
  Lemma big_andL_snoc Φ l x :
    ([∧ list] ky l ++ [x], Φ k y) ⊣⊢ ([∧ list] ky l, Φ k y) Φ (length l) x.
  Proof. by rewrite big_opL_snoc. Qed.

  Lemma big_andL_submseteq (Φ : A PROP) l1 l2 :
    l1 ⊆+ l2 ([∧ list] y l2, Φ y) [∧ list] y l1, Φ y.
  Proof.
    intros [l ->]%submseteq_Permutation. by rewrite big_andL_app and_elim_l.
  Qed.

The lemmas big_andL_mono, big_andL_ne and big_andL_proper are more generic than the instances as they also give l !! k = Some y in the premise.
  Lemma big_andL_mono Φ Ψ l :
    ( k y, l !! k = Some y Φ k y Ψ k y)
    ([∧ list] k y l, Φ k y) [∧ list] k y l, Ψ k y.
  Proof. apply big_opL_gen_proper; apply _. Qed.
  Lemma big_andL_ne Φ Ψ l n :
    ( k y, l !! k = Some y Φ k y ≡{n}≡ Ψ k y)
    ([∧ list] k y l, Φ k y)%I ≡{n}≡ ([∧ list] k y l, Ψ k y)%I.
  Proof. apply big_opL_ne. Qed.
  Lemma big_andL_proper Φ Ψ l :
    ( k y, l !! k = Some y Φ k y ⊣⊢ Ψ k y)
    ([∧ list] k y l, Φ k y) ⊣⊢ ([∧ list] k y l, Ψ k y).
  Proof. apply big_opL_proper. Qed.

No need to declare instances for non-expansiveness and properness, we get both from the generic big_opL instances.
  Global Instance big_andL_mono' :
    Proper (pointwise_relation _ (pointwise_relation _ (⊢)) ==> (=) ==> (⊢))
           (big_opL (@bi_and PROP) (A:=A)).
  Proof. intros f g Hf m ? <-. apply big_andL_mono; intros; apply Hf. Qed.
  Global Instance big_andL_id_mono' :
    Proper (Forall2 (⊢) ==> (⊢)) (big_opL (@bi_and PROP) (λ _ P, P)).
  Proof. by induction 1 as [|P Q Ps Qs HPQ ? IH]; rewrite /= ?HPQ ?IH. Qed.

  Lemma big_andL_lookup Φ l i x :
    l !! i = Some x ([∧ list] ky l, Φ k y) Φ i x.
  Proof.
    intros. rewrite -(take_drop_middle l i x) // big_andL_app /=.
    rewrite Nat.add_0_r take_length_le;
      eauto using lookup_lt_Some, Nat.lt_le_incl, and_elim_l', and_elim_r'.
  Qed.

  Lemma big_andL_elem_of (Φ : A PROP) l x :
    x l ([∧ list] y l, Φ y) Φ x.
  Proof.
    intros [i ?]%elem_of_list_lookup. by eapply (big_andL_lookup (λ _, Φ)).
  Qed.

  Lemma big_andL_fmap {B} (f : A B) (Φ : nat B PROP) l :
    ([∧ list] ky f <$> l, Φ k y) ⊣⊢ ([∧ list] ky l, Φ k (f y)).
  Proof. by rewrite big_opL_fmap. Qed.

  Lemma big_andL_bind {B} (f : A list B) (Φ : B PROP) l :
    ([∧ list] y l ≫= f, Φ y) ⊣⊢ ([∧ list] x l, [∧ list] y f x, Φ y).
  Proof. by rewrite big_opL_bind. Qed.

  Lemma big_andL_and Φ Ψ l :
    ([∧ list] kx l, Φ k x Ψ k x)
    ⊣⊢ ([∧ list] kx l, Φ k x) ([∧ list] kx l, Ψ k x).
  Proof. by rewrite big_opL_op. Qed.

  Lemma big_andL_persistently Φ l :
    <pers> ([∧ list] kx l, Φ k x) ⊣⊢ [∧ list] kx l, <pers> (Φ k x).
  Proof. apply (big_opL_commute _). Qed.

  Lemma big_andL_forall Φ l :
    ([∧ list] kx l, Φ k x) ⊣⊢ ( k x, l !! k = Some x Φ k x).
  Proof.
    apply (anti_symm _).
    { apply forall_introk; apply forall_introx.
      apply impl_intro_l, pure_elim_l⇒ ?; by apply: big_andL_lookup. }
    revert Φ. induction l as [|x l IH]=> Φ; [by auto using big_andL_nil'|].
    rewrite big_andL_cons. apply and_intro.
    - by rewrite (forall_elim 0) (forall_elim x) pure_True // True_impl.
    - rewrite -IH. apply forall_introk; by rewrite (forall_elim (S k)).
  Qed.
  Lemma big_andL_intro Φ l :
    ( k x, l !! k = Some x Φ k x) [∧ list] kx l, Φ k x.
  Proof. rewrite big_andL_forall //. Qed.

  Lemma big_andL_impl Φ Ψ m :
    ([∧ list] kx m, Φ k x)
    ( k x, m !! k = Some x Φ k x Ψ k x) -∗
    [∧ list] kx m, Ψ k x.
  Proof.
    rewrite -big_andL_forall -big_andL_and.
    by setoid_rewrite bi.impl_elim_r.
  Qed.

  Lemma big_andL_pure_1 (φ : nat A Prop) l :
    ([∧ list] kx l, φ k x) ⊢@{PROP} k x, l !! k = Some x φ k x.
  Proof.
    induction l as [|x l IH] using rev_ind.
    { apply pure_intro=>??. rewrite lookup_nil. done. }
    rewrite big_andL_snoc // IH -pure_and.
    f_equiv=>-[Hl Hx] k y /lookup_app_Some =>-[Hy|[Hlen Hy]].
    - by apply Hl.
    - apply list_lookup_singleton_Some in Hy as [Hk ->].
      replace k with (length l) by lia. done.
  Qed.
  Lemma big_andL_pure_2 (φ : nat A Prop) l :
     k x, l !! k = Some x φ k x ⊢@{PROP} ([∧ list] kx l, φ k x).
  Proof.
    rewrite big_andL_forall pure_forall_1. f_equivk.
    rewrite pure_forall_1. f_equivx. apply pure_impl_1.
  Qed.
  Lemma big_andL_pure (φ : nat A Prop) l :
    ([∧ list] kx l, φ k x) ⊣⊢@{PROP} k x, l !! k = Some x φ k x.
  Proof.
    apply (anti_symm (⊢)); first by apply big_andL_pure_1.
    apply big_andL_pure_2.
  Qed.

  Lemma big_andL_later Φ l :
     ([∧ list] kx l, Φ k x) ⊣⊢ ([∧ list] kx l, Φ k x).
  Proof. apply (big_opL_commute _). Qed.
  Lemma big_andL_laterN Φ n l :
    ▷^n ([∧ list] kx l, Φ k x) ⊣⊢ ([∧ list] kx l, ▷^n Φ k x).
  Proof. apply (big_opL_commute _). Qed.

  Global Instance big_andL_nil_persistent Φ :
    Persistent ([∧ list] kx [], Φ k x).
  Proof. simpl; apply _. Qed.
  Global Instance big_andL_persistent Φ l :
    ( k x, Persistent (Φ k x)) Persistent ([∧ list] kx l, Φ k x).
  Proof. revert Φ. induction l as [|x l IH]=> Φ ? /=; apply _. Qed.

  Global Instance big_andL_nil_timeless Φ :
    Timeless ([∧ list] kx [], Φ k x).
  Proof. simpl; apply _. Qed.
  Global Instance big_andL_timeless Φ l :
    ( k x, Timeless (Φ k x)) Timeless ([∧ list] kx l, Φ k x).
  Proof. revert Φ. induction l as [|x l IH]=> Φ ? /=; apply _. Qed.
End and_list.

Section or_list.
  Context {A : Type}.
  Implicit Types l : list A.
  Implicit Types Φ Ψ : nat A PROP.

  Lemma big_orL_nil Φ : ([∨ list] ky nil, Φ k y) ⊣⊢ False.
  Proof. done. Qed.
  Lemma big_orL_cons Φ x l :
    ([∨ list] ky x :: l, Φ k y) ⊣⊢ Φ 0 x [∨ list] ky l, Φ (S k) y.
  Proof. by rewrite big_opL_cons. Qed.
  Lemma big_orL_singleton Φ x : ([∨ list] ky [x], Φ k y) ⊣⊢ Φ 0 x.
  Proof. by rewrite big_opL_singleton. Qed.
  Lemma big_orL_app Φ l1 l2 :
    ([∨ list] ky l1 ++ l2, Φ k y)
    ⊣⊢ ([∨ list] ky l1, Φ k y) ([∨ list] ky l2, Φ (length l1 + k) y).
  Proof. by rewrite big_opL_app. Qed.
  Lemma big_orL_snoc Φ l x :
    ([∨ list] ky l ++ [x], Φ k y) ⊣⊢ ([∨ list] ky l, Φ k y) Φ (length l) x.
  Proof. by rewrite big_opL_snoc. Qed.

  Lemma big_orL_submseteq (Φ : A PROP) l1 l2 :
    l1 ⊆+ l2 ([∨ list] y l1, Φ y) [∨ list] y l2, Φ y.
  Proof.
    intros [l ->]%submseteq_Permutation. by rewrite big_orL_app -or_intro_l.
  Qed.

The lemmas big_orL_mono, big_orL_ne and big_orL_proper are more generic than the instances as they also give l !! k = Some y in the premise.
  Lemma big_orL_mono Φ Ψ l :
    ( k y, l !! k = Some y Φ k y Ψ k y)
    ([∨ list] k y l, Φ k y) [∨ list] k y l, Ψ k y.
  Proof. apply big_opL_gen_proper; apply _. Qed.
  Lemma big_orL_ne Φ Ψ l n :
    ( k y, l !! k = Some y Φ k y ≡{n}≡ Ψ k y)
    ([∨ list] k y